science technology and society - McNamara, Daniel Joseph,SJ; Valverde, Vida Mia; Beleno, Ramon III (Quezon City, Philippines ; C & E Publishing, Inc., 2018)
science technology and society discuss how science has influences human society and vice versa.
Includes bibliographical references and index.